(untitled) (Baghdad Science Journal, 2010)
The present study examined the effect of alcoholic extract of Camellia sinensis against Gram negative bacteria isolated from eyes infections (conjunctivitis), 25 specimens (39.68%) gave positive bacterial culture from a total of 63 samples. The bacteria detected includes Pseudomonas aeruginosa (12.69%), Enterobacter spp. (7.93%), Escherichia coli (6.34%), Moraxella spp. (4.76%), Proteus mirabilis (4.76%) and Klebsiella spp. (3.17%). The activity of the alcoholic extract of Camellia sinensis was also evaluated in the present study. The inhibitory ability of Camellia sinensis alcoholic extract against bacterial isolates at concentration (10,20,40,80,100)% showed the biggest average of inhibition zones diameters (25,23,23,17,15,13) mm at 100% concentration of P. aeruginosa, E.coli, Moraxella spp., Enterobacter spp., Klebsiella spp. and Proteus mirabilis isolates respectively. Different antibiotics were also used to compare their activities with the activity of Camellia sinensis alcoholic extracts.